Mendorong Generasi Z Menjadi Pelaku Ekonomi Kreatif Melalui Digital Marketing di Desa Manggis Boyolali - Ratna Safitri; Tri Mart Tianingsih; Yulia Artha Utami; Muhammad Afif Rasyid Hidayat; Unna Ria Safitri (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2026)
The development of the digital era is driving the growth of the creative economy and opening up significant opportunities for Generation Z, who are highly familiar with digital technology. This generation has the potential to become key players in the development of digital-based businesses if equipped with adequate knowledge and skills. The community service activity carried out in Ngemplak Village, Boyolali Regency, aims to equip Generation Z with an understanding and skills in digital marketing so they can play an active role in the creative economy. The activity was carried out through socialization methods and direct practice in managing an online store using the Shopee platform, supplemented by materials on the concept of the creative economy, digital business opportunities, online marketing strategies, and the use of social media as a promotional tool. The results of the activity showed an increase in participants' understanding of digital marketing, improved technical skills in managing online stores, and increased motivation and confidence to start independent businesses. This program is considered effective in encouraging the use of digital media as a productive tool that has economic value and is sustainable for Generation Z.